(untitled) (Research, Society and Development, 2020)
Hazard analysis and critical control points (HACCP) is a tool that allows the prevention of physical, chemical, and biological hazards through prevention. This analysis consists of conducting a survey of hazards at each stage of production and listing control measures for each identified hazard, eliminating hazards or reducing them to an acceptable level, is seen as one of the main tools that help industries to ensure safety of food. However, there is a shortage of discussions about the survey of hazards in rural dairy farms, and as industries increasingly demand qualifications to acquire a new supplier, this tool can help the producer to ensure the safety of milk, in addition to optimizing production through standardized processes. This study aims to elaborate a hazard analysis applicable to a dairy property located in the municipality of Sertão - RS. At the end of the study, control of the presence of antibiotics (PCC 1Q), physical particles larger than 2.0 mm (PCC 1F) and microbial multiplication (PCC 1B) was listed as critical control points, in addition to indicating several bottlenecks that could be restructured allowing the standardization of the process to maintain homogeneous milk production / quality.